Implementation of Preventive Maintenance for CNC Machines in Vocational Education Facilities: A Case Study at Politeknik Kampar - Romiyadi Romiyadi; Adi Febrianton (G-Tech: Jurnal Teknologi Terapan, 2025)
This research aims to optimize the preventive maintenance system for CNC machines in the context of vocational education, with a focus on improving practice efficiency and reducing downtime. The study was conducted at Politeknik Kampar using a quantitative-descriptive approach integrated with a case study method. Quantitative data were obtained from machine performance logs, including total operating hours, number of breakdowns, and maintenance time before and after preventive maintenance implementation. Descriptive data were gathered through structured interviews and direct observation of CNC training sessions. The research focused on two types of machines, namely the CNC Milling HURCO VM 10 and the CNC Turning Center SKT 160A, which are intensively used in practical training activities. Prior to the implementation of the preventive maintenance protocol, the existing maintenance system was reactive and unscheduled, leading to frequent breakdowns and extended operational downtime. Following the implementation of the preventive maintenance program over a six week period, the frequency of machine breakdowns decreased by approximately 45%, and average downtime was reduced from 6.2 hours to 3.4 hours per week. Consequently, practice efficiency increased by about 28%, as reflected in the higher completion rate of student machining tasks within the allocated schedule. Student involvement in daily maintenance also contributed to building practical awareness of the importance of maintenance in industrial settings. The findings demonstrate that preventive maintenance not only enhances machine reliability but also strengthens vocational learning processes based on hands-on skills.